The myth of job readiness? Written communication, employability, and the 'skills gap' in higher education. Issue 3 (4th March 2017) - Moore, Tim; Morton, Janne
Abstract : Recent developments in higher education have seen a strong emphasis placed on making graduates 'job ready' for their work in the professions. A driver of this agenda has been the many mass-scale surveys conducted with business and industry about the abilities and general employability of graduates. This Australian-based study is focused on perceptions and attitudes around one such ability – professional writing skills. 'Discourse-based interviews' were conducted with managers and supervisors from a range of professional areas. Their responses were most interesting, and served, among other things, to challenge some of the emerging ideas about 'job readiness' in current debates about the directions of higher education.